Holy Family. - Stone, George Eathl (photographer):::Creator::::::::::::
The image depicts a painting the Holy Family; the painting shows a powerful Mary taking over her child from Joseph. In the background on the right John the Baptist is visible, perhaps standing in a pool used for baptism. The frame is an ornately carved circular sculpture (1475 - 1564).